Student Perceptions of Source Credibility and Health-related Behavior : a Case Study - Collura, Grace; Hagerman, Carlie; Kitch, Jordan; Szpara, Claire; Xiong, Sheng (My University, 2013)
Previous research has shown that college students' intentions to perform health-related behaviors vary based on students' perception of credibility of the source providing the message (Jones, Sinclair & Courneya, 2003). The most available source of health information for college students is on-campus health services, however, studies have also shown that even though students are knowledgeable about the health services offered on college campuses, awareness does not necessarily translate into use (Fletcher, Bryden, Schneider, Dawson & Vandermeer, 2007). This study examined the perceptions of source credibility and level of trust among college students when seeking information on particular health needs offered on one Midwestern college campus.
Color poster with text and graphs.
Keywords: Trusted sources; Perceptions; College students; Health information; Posters